Ideas that matter : (The Ginger Press, 2011)
Jane Jacobs (1916-2006) is history's most celebrated urban critic. In addition to her classic, Death and Life of Great American Cities, Jacobs authored another half dozen influential books on urban planning, economics, and design. This title offers students, enthusiasts, and critics insights into the work of this seminal thinker.